2021
DOI: 10.1002/anie.202109518
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Constitutional Frameworks as Antibacterial and Antibiofilm Agents

Abstract: Dynamic constitutional frameworks (DCFs) were synthesized and screened for biofilm inhibition or disruption. They are composed of at rialdehyde core reversibly linked to adiamine PEG connector and to avariety of neutral, anionic, or cationic heads,t og enerate al ibrary of DCFs to generate multivalent dendritic architectures in the presence of Pseudomonas aeruginosa and Staphylococcus aureus.The best DCFs were always polycationic and the nature of the cationic heads significantly impact the antibiofilm activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…In the absence of AMF and heat treatment, Fe 3 O 4 NPs did not have any significant effect on the bacterial viability. The presence of Fe 3 O 4 @PEI NPs slightly decreased the number of viable cells due to the amino groups on the nanoparticle surfaces . It has been reported that amino groups could decrease the number of viable cells by destroying the integrity of the cell walls and altering the permeability of the cell membranes .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In the absence of AMF and heat treatment, Fe 3 O 4 NPs did not have any significant effect on the bacterial viability. The presence of Fe 3 O 4 @PEI NPs slightly decreased the number of viable cells due to the amino groups on the nanoparticle surfaces . It has been reported that amino groups could decrease the number of viable cells by destroying the integrity of the cell walls and altering the permeability of the cell membranes .…”
Section: Resultsmentioning
confidence: 96%
“…The presence of Fe 3 O 4 @PEI NPs slightly decreased the number of viable cells due to the amino groups on the nanoparticle surfaces. 46 It has been reported that amino groups could decrease the number of viable cells by destroying the integrity of the cell walls and altering the permeability of the cell membranes. 47 Moreover, the heat treatment did not notably improve the inhibitory efficiency of Fe Nanothermal particles have been found to be able to kill the cells.…”
Section: Resultsmentioning
confidence: 99%
“…Another forthcoming module of lowering toxicity wound is the use of dynamic constitutional frameworks (DCF) [ 227 ] that cause minimal to no cytotoxicity [ 228 ]. With reference to DCFs, a positive charge delivers better antibiofilm impact.…”
Section: Nanotechnology In Regenerationmentioning
confidence: 99%
“…With reference to DCFs, a positive charge delivers better antibiofilm impact. Moreover, surface charge density is pivotal in dendritic materials in order to generate wound biofilm hindrance [ 227 ]. Thus, tweezing the surface of nanosystems can also come in handy at the prospect of healing chronically infected injuries.…”
Section: Nanotechnology In Regenerationmentioning
confidence: 99%
“…Antibacterial agents involve antibiotics, natural extracts, cationic polymers, antimicrobial peptides, , and antibacterial materials. Most of them are not able to pass through the biofilm barriers efficiently, thus limiting their efficacies in the therapy of biofilm-associated infection. Mature biofilms act as barriers to antimicrobial agents by restricting their diffusion and preventing them from penetrating deeply into the matrix. Thus, novel therapeutic agents and strategies capable of fully accessing inside bacteria by penetrating the biofilm barriers for tackling biofilms are urgently needed .…”
Section: Introductionmentioning
confidence: 99%